Novel adaptive neural control design for a constrained flexible air-breathing hypersonic vehicle based on actuator compensation. (March 2016) - Bu, Xiangwei; Wu, Xiaoyan; He, Guangjun; Huang, Jiaqi
Abstract: This paper investigates the design of a novel adaptive neural controller for the longitudinal dynamics of a flexible air-breathing hypersonic vehicle with control input constraints. To reduce the complexity of controller design, the vehicle dynamics is decomposed into the velocity subsystem and the altitude subsystem, respectively. For each subsystem, only one neural network is utilized to approach the lumped unknown function. By employing a minimal-learning parameter method to estimate the norm of ideal weight vectors rather than their elements, there are only two adaptive parameters required for neural approximation. Thus, the computational burden is lower than the ones derived from neural back-stepping schemes. Specially, to deal with the control input constraints, additional systems are exploited to compensate the actuators. Lyapunov synthesis proves that all the closed-loop signals involved are uniformly ultimately bounded. Finally, simulation results show that the adopted compensation scheme can tackle actuator constraint effectively and moreover velocity and altitude can stably track their reference trajectories even when the physical limitations on control inputs are in effect. Highlights: The proposed controller is simpler than the ones derived from back-stepping. There is no need of analytic computation of time derivative of virtual controller. The computational burden is much lower than the existing studies׳. Auxiliary systems are developed to compensate the actuator saturation. The design can provide stable tracking performance when limitations are in effect.